PENGARUH KEPEMIMPINAN OTORITER DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT RPA NUSANTARA DI GUNUNG SINDUR, KABUPATEN BOGOR - Eva Wulandari; Bambang Sutarto (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of otoritary leadership  and work discipline on employee performance at PT RPA Nusantara in Gunung Sindur, Bogor Regency. The method used in this research is quantitative. The total of population is 126 the sample using saturated sampling, it was obtained as many as 66 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that otoritary  leadership has a significant effect on employee performance, this is evident from the results of the hypothesis test obtained t test > t table or 4.717> 1.668 with a significance value of 0.000 <0.05. Discipline also has a positive and significant effect on employee performance. Discipline also has a positive and significant effect on employee performance, this is evident from the results of the hypothesis test obtained t test > t table or 12.539> 1.668 with a significance value of 0.000 <0.05. Otoritary leadership and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 7.438 + 0.058 X1 + 684 X2. The otoritary leadership and work discipline have simultaneously a positive and significant effect on employee performance, this is can be seen from the results of the simultaneous test (F test) where the results of F test > F table 78.523> 3.24 with a significance value of 0.000 <0.05 based on the determination test, it is known that the R square value is 0.714. This shows that otoritary  leadership and work discipline contribute to employee performance by 71.4 while the remaining 28.6% is influenced by other factors not examined in this study.